DESIGN CONTROL AND MONITORING SYSTEM FOR BOILER WASTEWATER TREATMENT PROCESS USING PROGRAMMABLE LOGIC CONTROLLER AND HMI (HUMAN MACHINE INTERFACE) - Syahril Ardi; Sirin Fairus; Sekar Sukmaningrum (Universitas Mercu Buana, 2020)
Wastewater Treatment Plant (WWTP) is one of the infrastructures and systems in the manufacturing industry. This system serves to treat wastewater coming from boiler machines, which are used to produce steam to support the tire and tube production process of manufacturing companies, which are the object of our research. Wastewater from this boiler machine is alkaline and contains solids that are harmful to the ecosystem and the environment, so it needs to be processed so that wastewater can be discharged into drains. The process is not by following the standards; it can affect the quality of the process water so that water that is discharged into drains or water bodies violates government regulations. In this case, the pH standard of water is in a neutral state whose values are between 6 and 9 and is clear in color. Therefore, we conducted research that is designing a system to control and monitor the process at the wastewater treatment plant automatically. The design of this control system is done by adding sensors and actuators that are connected to the modular PLC that is the control system. This system is also designed to be connected to a PC (Personal Computer) as a monitoring system so that the process can be monitored continuously. Display interface created using HMI (Human Machine Interface) software. This is because many features that allow for a more attractive appearance. With this system, it can be sure that the boiler wastewater treatment process is more consistent and efficient in maintaining pH standards, and the process is monitored in real-time.